Distribution of the common frog Rana temporaria L. in subarctic Norway - Arne C. Nilssen; Karl-Birger Strann; Vigdis Frivoll (Fauna Norvegica, 1994)
The distribution of the common frog, Rana temporaria, in northernmost Norway was recorded by means of information given by people living in the different local communities. The records are given in a detailed map. Occurrences on islands and peninsulas were especially emphasized. The survey shows that R. temporaria is present on most of the biggest islands and on some small ones. The species is lacking on some medium-sized islands and peninsulas and on most small islands. Documentation on intentional introductions by humans was obtained in a few cases, and explains the somewhat “random” distributional pattern, especially on the archipelago of Helgeland in the southern part of North Norway. Other factors explaining the distribution in sub-arctic Norway are discussed.